Human salivary gustin is a potent activator of calmodulin-dependent brain phosphodiesterase. - Law, J S (1987)
Human salivary gustin stimulated activity of brain calmodulin-dependent cyclic nucleotide phosphodiesterase (cAMP PDEase; 3',5'-cyclic-nucleotide phosphodiesterase, EC 3.1.4.17) in a dose-dependent manner in the absence of calmodulin. At physiological levels found in human saliva, gustin activated cAMP PDEase 5- to 6-fold. Activation of PDEase occurred with as little as 500 ng of gustin. Comparative sensitivity of activation of PDEase by gustin was intermediate between calmodulin and lysophosphatidylcholine with maximal activation and half-maximal activation (indicated in parentheses) at 3 X 10(-8) M (4.3 X 10(-9) M), 3.4 X 10(-6) M (3.4 X 10(-7) M), and 2.5 X 10(-3) M (4.0 X 10(-5) M) for calmodulin, gustin, and lysophosphatidylcholine, respectively. No other major salivary protein activated PDEase. Anticalmodulin antibody completely inhibited calmodulin-activated cAMP PDEase activity, but the antibody had no effect on gustin-activated cAMP PDEase activity. A sensitive calmodulin RIA indicated that no calmodulin was detected in any gustin preparation that activated cAMP PDEase. Both gustin and calmodulin rendered cAMP PDEase thermally labile to a similar extent and increased Vmax without affecting the apparent Km for the substrate cAMP. Activation by gustin and calmodulin was unaffected by lubrol-PX, trypsin inhibitor, pepstatin A, or leupeptin. In the presence of 1 mM EGTA, gustin activated cAMP PDE 5- to 6-fold, but the activating ability was completely lost after gustin was heated at 100 degrees C for 5 min. In contrast, calmodulin lost all activating ability in the presence of 1 mM EGTA, whereas heating calmodulin at 100 degrees C for 5 min did not affect its activation of cAMP PDEase. Lysophosphatidylcholine-activation of cAMP PDEase, like gustin activation, was unaffected by EGTA, but lysophosphatidylcholine-activation of cAMP PDEase, like calmodulin activation, was unaffected by heating at 100 degrees C for 5 min.